Anatomic Variations of Mandibular Condyles in Brazilian Specimens - Fonseca, Roberta Maria Drumond Furtado Bossi; Schetino, Luana Pereira Leite; da Silva, Janice Henriques; Almeida-Leite, Camila Megale (Journal of Morphological Sciences, 2018)
Objective To describe the morphological characteristics and asymmetries between the left and right mandibular condyles in Brazilian cadaveric specimens.Material and Methods Thirty-two jaws were placed on a rigid support for image acquisition of the frontal and lateral views. The shapes of the mandibular condyles were classified, and measurements of the distance between the anatomical landmarks in the lateral and frontal views were performed.Results Mandibular length and width were not different between the right and left sides. Regarding the shapes of the mandibular condyles, the rounded type was the most frequent, followed by marked medial slope; flattened; overhanging lateral and medial slopes; downward flattening of both slopes and their merger in a single, extensive surface; and deformity and marked lateral slope with flaring and flattening. Asymmetry between the left and right mandibular condyles was present in 40% of the specimens.Conclusion The anatomy of mandibular condyles varies greatly, and this knowledge can avoid misdiagnosis by image examination of the anatomic variations.
Keywords: mandibular condyle; jaw; anatomic variation; temporomandibular joint